Promoting democracy: what role for the democratic emerging powers? - Gerd Schönwälder (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
This article examines the role of the democratic emerging powers - India, Brazil, South Africa, Indonesia, and Turkey - in promoting democracy beyond their own borders. It argues that while these countries have potential advantages compared to western democracy promoters, namely, their own experiences in transitioning from authoritarian to democratic rule and their greater familiarity with neighbouring non-democratic regimes, these advantages have not been realized due to fears of fostering political instability, damaging vital security and economic interests and creating inroads for extra-regional rivals. Explaining external democracy support policies as the result of shifting state preferences - seen as a complex amalgam of values, interests and structures of representation and power, which are in turn conditioned by surrounding regional and global environments - the article identifies four key factors that help explain the various commonalities and differences among the five cases studied, namely, recent memories of democratic transitions, the relative strength of democratic fabrics, the presence or absence of significant security challenges, as well as economic interests and the potential for regional expansion. The article concludes by arguing that a shift to a more proactive stance would require the democratic emerging powers to make some critical choices as to how to fill their new regional and global leadership roles. To influence these processes and to build viable partnerships, Western democracy promoters would need to acknowledge that the democratic emerging powers face distinct challenges, while insisting on commonly held democratic standards and principles.
Keywords: 330; Aufstrebende Mächte; Sicherheit; Frieden und fragile Staaten; Demokratie und Autokratie